1997
DOI: 10.1177/216507999704500905
|View full text |Cite
|
Sign up to set email alerts
|

Farm Worker Injuries Associated with Cows

Abstract: recent overview of agricultural occupational safety and health hazards reported the incidence of trauma due to farm animals as "unknown" (OSHA, 1994), possibly due to the attention given to machine related injuries. A study based on National Safety Council data estimated that animal induced injuries amount to 16.9% of all farm work injuries (Purschwitz, 1990). However, in a recent dairy farming study, 32% of injuries were reported as animal related (Pratt, 1992). Among hospitalized victims of agricultural inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 5 publications
3
17
0
Order By: Relevance
“…There have been many local or regional surveys that have looked at risk to farm animal handlers (Stallones, 1990;Brison & Lawrence, 1992;Pratt et al, 1992;Waller, 1992;Zhou & Roseman, 1994;Layde et al, 1996;Boyle et al, 1997;Casey et al, 1997a;Casey et al, 1997b;Hwang et al, 2001;Sprince et al, 2003;Douphrate et al, 2009). Most of the studies show that livestock handling activities are the second or third leading cause of injuries on the farm, causing from 12% to 24% of farm injuries.…”
Section: Epidemiologymentioning
confidence: 99%
“…There have been many local or regional surveys that have looked at risk to farm animal handlers (Stallones, 1990;Brison & Lawrence, 1992;Pratt et al, 1992;Waller, 1992;Zhou & Roseman, 1994;Layde et al, 1996;Boyle et al, 1997;Casey et al, 1997a;Casey et al, 1997b;Hwang et al, 2001;Sprince et al, 2003;Douphrate et al, 2009). Most of the studies show that livestock handling activities are the second or third leading cause of injuries on the farm, causing from 12% to 24% of farm injuries.…”
Section: Epidemiologymentioning
confidence: 99%
“…Studies have been conducted for better understanding the main causes of accidents in agriculture [11][12][13]. According to Swedish research, there are three defined factors that influence risk and safety during contact and working with animals: the human (handler), the animal (cattle), and the facilities.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Douphrate et al (2006Douphrate et al ( , 2009 found that cattle-handling injuries in Colorado often occurred when dairy workers were either kicked or stepped on while milking. Similarly, Casey et al (1997b) found that dairy workers in New York State were frequently injured while washing udders or attaching milking equipment. These findings raise the possibility that injuries might be prevented through the redesign of milking equipment and procedures.…”
mentioning
confidence: 99%
“…In beef and dairy settings overall, injuries have been especially common where workers and cattle are crowded together in barns, alleys, and pens (Casey et al, 1997a(Casey et al, , 1997bDouphrate et al, 2006Douphrate et al, , 2009Grandin, 1997). This realization has led to calls for improved physical barriers and new work procedures designed to keep cattle calm and separated from their handlers (Grandin, 1997;NCR-197, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation